Performance of porous asphalt incorporating cellulose fiber - Nurul Syazni, Othman (2019)
Porous Asphalt (PA) has an open structure layer compared to dense asphalt mixture. Thus, PA can increased the safety during rainfall due to its open structure water. But, PA have weakness in terms of stability and durability due to large amount of air voids. Therefore, in this study, Cellulose Fiber (CF) were mix with the binder to improve the properties of PA and the type of CF used was in pellets type. CF known as a stabilizing agent that have higher asphalt content, thick film coating and higher mix stability. Thus, CF has ability to improve the strength of PA. This study focuses on the existence of CF in following order 0% (as a unmodified sample), 0.2%, 0.3%, 0.4%, 0.5% and 0.6%.The aim for this study is to investigate the effect of CF on engineering properties of PA grading B. The laboratory test involved to evaluate the performance of CF-PA were Abrasion, Marshall Stability, Resilient Modulus and Dynamic Creep. The Abrasion test to evaluate surface strength CF and PA bind together with asphalt binder and the result shows that higher surface strength at the addition of 0.4% CF. For the stability test, it to evaluated the maximum load can applied to PA before failure happened and it influenced by the density of PA. Therefore, the result of testing shows at higher value of stability and density at addition of 0.6% CF. Moreover, the resilient modulus test determine how CF influenced by traffic loading and temperature condition. Thus, the result at 0.6% CF the higher value of resilient modulus at traffic loading and temperature condition. Lastly, the performance test for dynamic creep to determine the resistance of asphalt mixture to rutting at 25˚C and the best sample at 0.2% CF. Thus, the existence of CF is capable enhancing the performance of PA. For the future study, it is recommend to analyze the mechanical behavior and microstructural of PA with existence of CF in type of loose form in order to known their stabilizing in PA.